2022
DOI: 10.1177/15353702221080435
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 regulates starvation-induced autophagy through the STAT3-mTOR-p70s6k axis in hepatic stellate cells

Abstract: The degree of activation of hepatic stellate cells (HSCs) is closely related to the level of autophagy in HSCs. We previously showed that interleukin-10 (IL-10) strongly inhibits HSC activation in rat fibrotic liver. However, little is known about the effect of IL-10 on HSC autophagy. For investigation of the effect of IL-10 on starvation-induced autophagy in immortal rat hepatic stellate cells (HSC-T6) and the molecular mechanism, HSC-T6 cells were incubated with serum-free DMEM for different periods and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Furthermore, acinar cell vacuolization in pancreatitis models is associated with accumulation of p62, indicating that autophagic flux is impaired [ 45 ]. IL-10, a member of the IL-10 family, suppresses autophagosome formation via activation of STAT3 [ 46 ]. Meanwhile, the role of IL-19 in autophagy remains to be unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, acinar cell vacuolization in pancreatitis models is associated with accumulation of p62, indicating that autophagic flux is impaired [ 45 ]. IL-10, a member of the IL-10 family, suppresses autophagosome formation via activation of STAT3 [ 46 ]. Meanwhile, the role of IL-19 in autophagy remains to be unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, IL-10 inhibits the formation of autophagosomes in hepatic stellate cells induced by oxidative stress by activating the mTOR-STAT3 signaling pathway, thereby suppressing the brosis process (44). In NAFLD, IL-10 alleviates brosis by inhibiting the activation of hepatic stellate cells, regulating the expression of autophagyrelated proteins, and affecting signaling pathways (45).In vitro studies have found that IL-10 can inhibit hydrogen peroxide (H2O2)-induced autophagy in hepatic stellate cells, thereby reducing autophagic activity in brotic livers and HSCs (44). IL-10 promotes liver repair and regeneration, while also inhibiting hepatocyte apoptosis, thereby reducing liver damage and brosis (46,47,48).…”
Section: Discussionmentioning
confidence: 99%